2011
DOI: 10.1049/iet-gtd.2010.0779
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic harmonic domain modelling of synchronous machine and transmission line interface

Abstract: This study presents a methodology for analysing the transient behaviour of harmonics associated with the interfacing of a synchronous generator and a transmission line. The algorithm is derived entirely in the dynamic harmonic domain that is based on an orthogonal basis and on operational matrices. The main characteristics of the proposed method are: its capability to accurately follow the harmonic content of a transient without the aid of a post-processing tool and its ability to serve as a visually active in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In other contributions [50]- [52] a Newton method is proposed based on the instantaneous power balance formulation for the representation of linear and nonlinear loads. While the DHD modeling of individual power system elements is relatively straightforward, the interfacing of several components [50] is still quite challenging, and is an ongoing topic of research.…”
Section: ) Dynamic Harmonic Domain Methods (Dhd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In other contributions [50]- [52] a Newton method is proposed based on the instantaneous power balance formulation for the representation of linear and nonlinear loads. While the DHD modeling of individual power system elements is relatively straightforward, the interfacing of several components [50] is still quite challenging, and is an ongoing topic of research.…”
Section: ) Dynamic Harmonic Domain Methods (Dhd)mentioning
confidence: 99%
“…Detailed models of power system components, such as the synchronous machine [26]- [28], the power transformer [21], [29]- [32], arc furnaces [33], fluorescent lamps [33], [34], Thyristor Commutated Reactors (TCRs) [35], the power converter [36]- [39], HVDC systems [40], [41], adjustable speed drives (ASDs) [42], static var systems (SVSs) [43], the unified power flow controller (UPFC) [44], the static compensator (STATCOM) [45], the Static Synchronous Series Compensator (SSSC) [46] and for the interaction between generation and transmission systems [47]- [50] have been developed in the HD.…”
Section: ) Linearize Each Nonlinear Component In the Harmonicmentioning
confidence: 99%
“…The DHD has been applied to flexible alternating current transmission system devices, synchronous machines, and transmission lines. 18,26,28,29,[30][31][32][33] Ramirez 34 proposed a modified HD to incorporate interharmonics. A modeling and simulation method for a large direct current power electronic system by using harmonic state-space modeling is put forward by Kwon et al 35 Through this method, the required computation time and CPU memory can be reduced, where this faster simulation can be an advantage of a large network simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed DHD methodology has been demonstrated by its application to the study of the dynamic behavior of harmonics in HVDC [14], STATCOM [23], TCR [24], SVC [25,26], SSSC [25,26] and UPFC [25,26] systems, and has shown that DHD models have none of the disadvantages associated with WFFT and therefore it is a possible method to be used for the accurate assessment of power quality [23]. Recently, the DHD modeling has been successfully applied for several applications in transmission and distribution systems [27][28][29][30][31][32]. The DHD modeling approach can also be applied to multi-phase, multi-machine systems.…”
Section: Introductionmentioning
confidence: 99%